Linking plant phenology to conservation biology - Morellato, Leonor Patrícia Cerdeira [UNESP]; Alberton, Bruna [UNESP]; Alvarado, Swanni T. [UNESP]; Borges, Bruno [UNESP]; Buisson, Elise; Camargo, Maria Gabriela G. [UNESP]; Cancian, Leonardo F. [UNESP]; Carstensen, Daniel W. [UNESP]; Escobar, Diego F.E. [UNESP]; Leite, Patrícia T.P. [UNESP]; Mendoza, Irene [UNESP]; Rocha, Nathália M.W.B. [UNESP]; et al. (Elsevier, 2016)
Phenology has achieved a prominent position in current scenarios of global change research given its role inmonitoring and predicting the timing of recurrent life cycle events. However, the implications of phenology to environmental conservation and management remain poorly explored. Here,we present the first explicit appraisal of howphenology-amultidisciplinary science encompassing biometeorology, ecology, and evolutionary biology- can make a key contribution to contemporary conservation biology. We focus on shifts in plant phenology induced by global change, their impacts on species diversity and plant-animal interactions in the tropics, and how conservation efforts could be enhanced in relation to plant resource organization. We identify the effects of phenological changes and mismatches in the maintenance and conservation of mutualistic interactions, and examine how phenological research can contribute to evaluate, manage and mitigate the consequences of land-use change and other natural and anthropogenic disturbances, such as fire, exotic and invasive species. Wealso identify cutting-edge tools that can improve the spatial and temporal coverage of phenological monitoring, from satellites to drones and digital cameras. We highlight the role of historical information in recovering long-term phenological time series, and track climate-related shifts in tropical systems. Finally, we propose a set of measures to boost the contribution of phenology to conservation science.Weadvocate the inclusion of phenology into predictive models integrating evolutionary history to identify species groups that are either resilient or sensitive to future climate-change scenarios, and understand how phenological m ismatches can affect community dynamics, ecosystem services, and conservation over time.
Keywords: Climate change; Management; Monitoring; Plant-animal interactions; Resource availability; Restoration ecology